Gas sensitivity of WOx/WS2 nanocomposites at room temperature under ultraviolet irradiation - Z.V. Shomakhov; S.S. Nalimova; O.D. Zyryanova; V.M. Kondratev; Z.Kh. Kalazhokov; C.D. Bui; V.A. Moshnikov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
Currently, semiconductor gas sensors are of interest for various applications, including industry, medicine and environmental monitoring. One of the most important tasks in the sensor technology is to reduce the operating temperature of devices. In this paper, it is proposed to use WOx/WS2 nanostructures obtained by a hydrothermal method to solve this problem. The morphology, structure, and composition of the developed nanostructures were studied using scanning electron microscopy, reflected electron diffraction and X-ray photoelectron spectroscopy. It is shown that the nanostructures are formed by 1D and 2D nanoobjects with an average length of 200 nm and are nanocomposites consisting of tungsten oxide WOx and tungsten disulfide WS2. The study of sensory properties when exposed to isopropanol, ethanol and acetone vapors at room temperature was carried out. A reversible change in resistance is demonstrated when these gases appear in the atmosphere. Additionally, exposure to ultraviolet radiation during the measurement process leads to an increase in the response value and speed of the sensor layers in the case of interaction with isopropanol and ethanol vapors.